2009
DOI: 10.1021/ja900941k
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Construction of Seven-Membered Rings with an All-Carbon Quaternary Center by Direct Tiffeneau−Demjanov-type Ring Expansion

Abstract: Insertion of one methylene unit into the C-C bond of cyclohexanones is a potentially useful, straightforward method for the construction of seven-membered carbocycles. An especially appealing but largely unexplored method in this arena is the nucleophilic addition of diazoalkanes to the Lewis acid-activated cyclohexanones and subsequent ring expansion accompanied by the extrusion of nitrogen (direct Tiffeneau-Demjanov-type ring expansion). Our primary finding is the unprecedented insertion of alpha-alkyldiazoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…On the other hand, the corresponding formal CC bond insertion (Scheme , when R′=alkyl or aryl) is more challenging because of the relatively low reactivity and the difficulty associated with the selectivity of the 1,2‐shift. Recently, the studies by Kingsbury,1g, 2e,h,j Maruoka,1f, 2d,f,g,i Feng,1h, 2k and other groups have significantly promoted the development of this area, particularly the stereocontrol of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the corresponding formal CC bond insertion (Scheme , when R′=alkyl or aryl) is more challenging because of the relatively low reactivity and the difficulty associated with the selectivity of the 1,2‐shift. Recently, the studies by Kingsbury,1g, 2e,h,j Maruoka,1f, 2d,f,g,i Feng,1h, 2k and other groups have significantly promoted the development of this area, particularly the stereocontrol of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In ap revious communication, [10] we showed that two differentd oubleb ond regioisomers-theo lefination product A or the reductivea lkenylation derivative B,r espectively,c an be obtained depending on the nature of both coupling partners, and in at otally predictable manner (Scheme1a). Interestingly,i nasingle particular example when a4 -substituted cyclohexanonew as employed, the coupling reactionp roceeded with total diastereo-selectivity leading to the reductive alkenylation product as as ingle diasteroisomer.Iti snoteworthy that an important limitation of the reactions basedo ns ulfonylhydrazoneso rd iazo compounds that proceed without the need of am etal catalyst is their lack of stereocontrol; [11] therefore, this particular reaction was indeed ar are example of ad iastereoselective reaction based on diazo compounds in the absence of am etal catalyst. [12] Ta king into consideration the ample synthetic possibilities that these reductivec ouplings offer,w ed ecided to investigate in more detail the stereoselectivity of these metal-free Csp 3 À Csp 2 bond-forming reactions.…”
mentioning
confidence: 99%
“…The activation of diazo compounds for carbene‐transfer chemistry is commonly achieved by using oxidized transition‐metal complexes/salts. Recently, Maruoka was able to show that BF 3 is also a potent Lewis acid catalyst for diastereoselective Tiffeneau–Demjanov‐type ring expansions (Scheme ) 29. This report certainly represents an important expansion in the field of boron catalysis, as it showcases the fact that under certain conditions boron‐containing complexes can possess metal‐like reactivities.…”
Section: Catalysis By Means Of Biorelevant Metalsmentioning
confidence: 79%